Migration to advanced maintenance and monitoring techniques in the process industry - Fabricius, Stefan; Badreddin, Essameddin; Kröger, Wolfgang (Condition monitoring and diagnostic engineering management, 2001)
Collaboration with an industry partner provides us with insight in current maintenance and monitoring practice in the process industry. We observe that preventive maintenance is clearly favoured over the breakdown strategies of past decades and that condition-based maintenance using off-line inspection methods is quite established. Online, real-time monitoring techniques on the other hand, are still rare and have not extensively spread so far. There seems to be a gap between promising research ideas in the field of process monitoring and their practical application. This text investigates the reasons for rather slow industrial adoption of available monitoring methodology and proposes remedial action. The demand for more flexible, modular, easier-to-implement, maintainable and cost-efficient monitoring schemes is stressed. Especially in process industry, with production facilities often running at various operating points for different products and rather frequent modifications to the plant itself, adaptable and balanced schemes are thought necessary. To support decisions about cost-efficient introduction of monitoring programs, plant modelling can prove useful. A modelling concept is presented which accounts for all important aspects of entrepreneurial systems including material, energy, information and monetary flows. It is intended to aid in mastering the ever increasing complexity of modern technical systems not only on the component, but on system level as well.